Business adoption of digital marketing dashboards - Shaikh, Sohail (My University, 2018)
The study was focused on investigating when and how business executives adopt digital dashboards. The research set out to establish the drivers and obstacles of dashboard adoption, and how different variables affect the rate of adoption. The findings of the study confirmed that user interface sub-items such as visual attractiveness, clarity and intuitiveness as well as clear communication and frequent training are the key factors that business executives put into consideration when making the decision on whether or not to adopt digital marketing dashboards. Results of the quantitative data indicated that the reliability of data and the ability to customize it has little to insignificant effect on dashboard adoption and sustainability. However, the major limitation of the thesis is that the study was limited to performance dashboard in the marketing departments. This makes it impossible to generalize findings to other departments such as procurement and finance, whose needs differ from that of the marketing department. Furthermore, only one case company was used, where the researcher interned as a Digital Marketing Analyst. It is possible that had the study included more participants from other companies, the results would have shown more diverse factors that influence adoption and sustainability of digital dashboards. Overall, this study contributes to the marketing and information system literature by providing evidence on variables that affect adoption rates, use and the benefits of digital marketing dashboards. The researcher recommends that more case studies on different companies about when and how business executives adopt digital dashboards as well as the comparison of factors that influence adoption and sustainability in different departments will greatly contribute to the current findings. Furthermore, future researchers should study how digital dashboards are used in other industries. This is because recently, the trend has been continuously shifting from static reporting and analysis to a more dynamic and interactive visual reporting that all users can easily access at all times regardless of their geographical location.
Keywords: Marketing, digital dashboards, adoption